- PENGAKUAN TANAH ULAYAT MASYARAKAT HUKUM ADAT UNTUK PEMBANGUNAN NASONAL : - - Nadia Elvin (Jurnal Hukum Lex Generalis, 2024)
This research aims to describe the extent to which legal pluralism can run along with the times towards the recognition of customary land of indigenous peoples used as a means of national development. In formal legality, customary land rights of indigenous peoples have a place in national land law, but at the level of law in action they still lack legal protection. Without the availability of adequate land, planned development programs cannot run and ongoing development projects will be stalled. The government must participate in protecting the customary land rights of indigenous peoples who have long occupied their territory. This study uses a qualitative legal study method with a literature study research type. The approach used is customary law pluralism using documentation data collection techniques. The result of this study is that the existence of legal pluralism on customary land makes the law apply side by side for areas where there are customary rights. As for areas where there is no customary right, national agrarian law applies